The Influence of Direct and Overheard Messages on Children's Attitudes Toward Novel Social Groups. Issue 3 (30th March 2019) - Lane, Jonathan D.; Conder, Emily B.; Rottman, Joshua
Abstract : Individuals often develop negative biases toward unfamiliar or denigrated groups. Two experimental studies were conducted to investigate the extent to which brief negative messages about novel social groups influence children's (4‐ to 9‐year‐olds'; N = 153) intergroup attitudes. The studies examined the relative influence of messages that are provided directly to children versus messages that are overheard and examined whether the force of these messages varies with children's age. According to implicit and explicit measures of children's intergroup attitudes, children rapidly internalized messages demeaning novel groups, thus forming negative attitudes toward outgroups merely on the basis of hearsay. These effects were generally stronger among older children, and were particularly pronounced when the message was provided directly to children.